Quality and Antioxidant Activity of Yogurt Supplemented with Roselle during Cold Storage - El Latifa Sri Suharto; Irma Isnafia Arief; Epi Taufik (Faculty of Animal Science, Bogor Agricultural University, 2016)
The purpose of this study was to determine the quality (physical, chemical, microbiological characteristics), total phenolic content, and antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) inhibition assay of probiotic yogurt supplemented with roselle flower extract (Hibiscus sabdariffa L) during cold storage. The experiment used treatment for types of yogurt as follows: cow’s milk probiotic yogurt + roselle, goat’s milk probiotic yogurt + roselle, cow’s milk yogurt, and goat’s milk yogurt. The yogurt was stored in cold storage and evaluated the quality and antioxidant activity variables on days 0, 3, 6, 9, 12, and 15th. The results showed that there were interaction (P<0.05) between types of yogurt and storage time on pH value and total lactic acid bacteria (LAB), but no interaction effect on viscosity. The types of yogurt significantly affected (P<0.05) aw, total titrable acid (TTA), total phenolic content, and antioxidant activity. Cow’s milk probiotic yogurt + roselle and goat’s milk probiotic yogurt + roselle were the best yogurt that contributed to a good quality and high antioxidant activity up to 15 d at cold storage.